Daily field checking list by Walter Rosene, January 26, 1941 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed at Boxholm and Grand Junction by Walter Rosene and Robert Walker, January 26, 1941. Also notes there was nearly a foot of snow on the ground. Plustek--flatbed